Tradisi â€œNgayahâ€ sebagai Wadah Komunikasi Masyarakat Hindu Perspektif Pendidikan Humanis-Religius - Pitriani, Ni Rai Vivien (Institut Hindu Dharma Denpasar, 2020)
The writing of this article is done to reveal the tradition of ngayah as a communication forum for Hindu society in the perspective of religious humanist education. The results of this study reveal that the ngayah tradition that is usually carried out by the Hindu community in Bali is governed by customary law, customary law in Bali is a rule that regulates the habits of the Hindu community in Bali. The rules contained in Balinese customary law are based on Hindu religious teachings. The Ngayah tradition is the local wisdom of the Balinese people in which local cultural communication occurs. The community in carrying out this tradition obeys customary laws starting from the discipline of the kulkul voice as a sign of the time to start ngayah to making upakara facilities in accordance with local customs and sincere to follow and undergo any series of ceremonies in the ngayah tradition. Not only obeying customary law but also in the tradition of ngayah as a means of communication for the community to be able to build good communication, get to know each other, build intimacy, learn to socialize, have ethics, be polite in speaking and get to know the character of the community in the neighborhood. The ngayah tradition is an implementation of religious humanist education, in this case humanist education which emphasizes the aspect of individual independence is integrated with religious education in order to build an individual-social life that has independence, but without leaving religious values.